2022
DOI: 10.26603/001c.31651
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Validity and Reliability of Two-dimensional Frontal Plane Knee Measurements during Multi-directional Cutting Maneuvers

Abstract: Background Excessive knee valgus has been strongly suggested as a contributing key factor for anterior cruciate ligament (ACL) injuries. Three-dimensional (3D) motion analysis is considered the “gold standard” to assess joint kinematics, however, this is difficult for on-field assessments and for clinical setting. Purpose To investigate the concurrent validity of 2D measurements of knee valgus angle during cutting in different directions and to explore intra-rater and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
(30 reference statements)
0
4
1
4
Order By: Relevance
“…Another possible explanation for the high ICC value is that current study participants frequently perform COD manoeuvres in their sport, reducing variabilities. When comparing the present study to another study used two-dimensional analysis, the results showed that the ICC for knee abduction angle was 0.92 in 90° COD manoeuvres, which was slightly better than the current study (ICC=0.89) (46). In addition, VGRF showed a high reliability value with low measurement error in both tasks (90°, 135°) compared to other kinematics and kinetics outcomes.…”
Section: Discussioncontrasting
confidence: 56%
“…Another possible explanation for the high ICC value is that current study participants frequently perform COD manoeuvres in their sport, reducing variabilities. When comparing the present study to another study used two-dimensional analysis, the results showed that the ICC for knee abduction angle was 0.92 in 90° COD manoeuvres, which was slightly better than the current study (ICC=0.89) (46). In addition, VGRF showed a high reliability value with low measurement error in both tasks (90°, 135°) compared to other kinematics and kinetics outcomes.…”
Section: Discussioncontrasting
confidence: 56%
“…Permainan basket banyak melakukan gerakan yang memanfaatkan kaki sehingga membuat risk of injury pada knee yang menjadi pusat tumpuan saat melakukan landing dan cutting (Anderson et al, 2016). Knee injury terjadi karena non-contact dengan mekanisme knee valgus (Irawan et al, 2022). Risk of injury pada anggota gerak bawah lebih sering dialami pada olahraga lapangan kecil dibandingkan lapangan besar pada usia SMA, hal ini berdasarkan (Chussurur, 2015).…”
Section: Pendahuluanunclassified
“…Parameter yang digunakan dalam penelitian ini Frontal Plane Projection Angle (FPPA) dengan pengukuran 2D menggunakan aplikasi Kinovea untuk menilai pola gerak yang beresiko menimbulkan cedera. Nilai reabilitas parameter ini memiliki nilai antar penilaian (ICC kumulatif: 0.821-0.937) dan intra-penilai yang baik (ICC kumulatif: 0.970-0.987) hal ini menunjukan bahwa validitas dan FPPA (Frontal Plane Projection Angle) dengan menggunakan pengukuran 2D adalah baik (Irawan et al, 2022). Pengukuran 2D dilakukan dengan merekam menggunakan dua kamera webcam logitech resolusi 60fps dengan ketinggian 60 cm dan jarak 2 meter dari lintasan yang langsung dihubungkan ke laptop untuk langsung di olah ke dalam software kinovea.…”
Section: Pengukuran 2dunclassified
See 1 more Smart Citation
“…Gambar 1. Setting drop landing task(Irawan et al, 2022) Prosedur pengambilan data untuk hari pertama diawali dengan tahap persiapan yang berupa meminta persetujuan untuk mengisi informed consent dengan menjelaskan mekanisme penelitian dan tujuan penelitian. Untuk hari kedua setelah setuju mengikuti penelitian sesuai kriteria inklusi dan kuisioner, subjek melakukan pemanasan terlebih dahulu sebelum melakukan penelitian, selanjutnya diberi stiker marker untuk mempermudah pengolahan data pada software kinovea, terdapat 3 titik marker yaitu pada Spina illiaca anterior superior (SIAS), tuberositas tibialis, dan talus.…”
unclassified